Simplify:
$x^2 (x-y) y^2 (x + 2y)$


Given:

$x^2 (x-y) y^2 (x + 2y)$

To do:

We have to simplify the given expression.

Solution:

$x^2 (x-y) y^2 (x + 2y)=x^2y^2 (x - y)(x + 2y)$

$= x^2y^2 (x^2 + 2xy - xy - 2y^2)$

$= x^2y^2(x^2 + xy - 2y^2)$

$= x^2y^2(x^2)+x^2y^2(xy) - x^2y^2(2y^2)$

$= x^{2+2}y^2+x^{2+1}y^{2+1} - 2x^2y^{2+2}$

$=x^4y^2 + x^3y^3 - 2x^2y^4$

Tutorialspoint
Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

42 Views

Kickstart Your Career

Get certified by completing the course

Get Started
Advertisements